Factors Related to Eye Fatigue on Computer User Workers at PT. Krakatau Bandar Samudera in 2022 - Maman Sutisna; Ela Nurdiawati; Dini Daningrum; Nurce Arifiati; Sita Oktafiani Eka Putri; Prihayati Prihayati (AGUSPATI Research Institute, 2023)
Eye fatigue is a strain on the eyes or visuals caused by the use of the sense of sight in jobs that require the ability to see for long periods, accompanied by uncomfortable viewing conditions. This study aimed to determine the factors associated with eye fatigue in computer user workers at PT. Krakatau Bandar Samudera in 2022. The design of this research is cross-sectional. The research population is all computer user workers totaling 168 respondents with a sample of 86 respondents taken by simple random sampling. Primary data collection using questionnaires, interviews, and observations, while secondary data was obtained from company profiles. Data analysis was carried out univariate and bivariate with the Chi-Square test. The results of the univariate analysis showed that from 86 respondents, 72 (83.7%) experienced complaints of eye fatigue, eye rest with risky time (<15 minutes) as many as 53 (61.6%), Eye Refractive Disorders 50 (58.1%) respondents, the lighting level does not meet the requirements as much as 16 (18.6%) respondents and the monitor height is not optimal as much as 3 (3.5%) respondents. The bivariate analysis results stated that there was a significant relationship between eye rest (P-value=0.000), eye refractive error (P-value=0.001), and eye fatigue. There is no significant relationship between lighting levels (P-value 0.295), monitor height (P-value = 0.415), and complaints of eye fatigue. Research advises, that the company implements lighting in the workspace according to the standard, namely a minimum of 300 lux, so it is necessary to take care of the lights that are out and gloomy.